Transformational leadership and knowledge sharing: Science mapping of present and future trend - Hasan, Mohd Najmuddin; Christine Tan Nya-Ling; Wider, Walton; Ahmad Samed Al-Adwan; Chong, Chin Wei; Lester Naces Udang; Fauzi, Muhammad Ashraf (Environment and Social Psychology, 2026)
This study explores and synthesizes the knowledge structure of transformational leadership on knowledge sharing. Transformational leadership has been widely recognized as an effective approach for fostering knowledge sharing among individuals within organizations, although its impact may vary depending on contextual factors. Through a science mapping analysis, this study reviews the fundamental knowledge structure in the Web of Science (WoS) database to uncover the current and future trends of transformational leadership and knowledge sharing. A total of 441 documents were retrieved from the Web of Science (WoS), spanning the years 2006 to 2024. The current trends produced by bibliographic coupling analysis depicted three clusters: Leadership influence on employees’ creativity, social capital and knowledge sharing behavior, and innovation capability through transformational leadership. At the same time, the future trends produced by co-word analysis suggest three themes associated with 1) firm performance, 2) innovation and creativity, and 3) fostering of trust, absorptive capacity, and self-efficacy through transformational leadership. Implications suggest that transformational leadership is one of the most effective leadership styles that encourages followers’ knowledge sharing behavior, among other constructive leadership styles, such as servant transactional leadership, servant leadership, and authentic leadership. Organizations need to develop transformational leadership among their leaders to ensure that followers can follow and replicate the ideas of their leaders. This study is among the first to present the knowledge structure on transformational leadership and its relationship with knowledge sharing.